Pengaruh Blower Terhadap Hasil Uji Kadar Emisi Gas Buang (CO, HC, NOx, Asap) Berbasis Mikrokontroler - SITI SHOFIAH (Universitas Muhammadiyah Tangerang, 2023)
Motorized vehicles produce 60-70% of the largest air pollution compared to industry which only produces 10-15%. The working process of vehicles produces major pollutants in the form of nitrogen oxides (NOx), carbon monoxide (CO), sulfur oxides (SO2), hydrocarbons (HC) and lead (Pb). Motor vehicle emissions can affect motor vehicle inspection facilities from a health perspective. This research was conducted at exhaust emission locations, elevator shafts and brake test equipment with emission level gauges equipped with sensors MQ2, MQ7, MQ135, DHT11, TGS2611 and blowers to standardize emission levels (CO, HC, NOx, smoke and room temperature). ) This study aims to monitor and standardize CO, HC, NOx and smoke levels. Based on the research, it has been obtained data from emission reduction tests (CO, HC, NOx and smoke) based on a microcontroller which has been successfully implemented using a blower. The results showed that after the blower was turned on, the concentrations of CO, HC and smoke decreased the most in the brake tester room, namely 1.95 ppm, 2.06 ppm and 1.21 ppm, while the highest decrease in NOx levels occurred in the pit lift of 82 ppm.